2022
DOI: 10.1002/admi.202101699
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Prominent Li+ Intercalation Process of Metal Sulfide Catalyst in Li‐S Batteries

Abstract: and its discharge products (Li 2 S 2 /Li 2 S) are poor and will largely hinder the reaction kinetics of Li-S system; while the dissolution and migration of lithium polysulfides (LiPS) will lead to undesired shuttle effects and poor cycle life, all of which will hamper the large scale application of Li-S batteries. [7][8][9] In the view of the above problems, scientists have done a lot of exploration on improving the reaction dynamics. A series of carbon materials, such as meso/ microporous carbon, carbon nanot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In Li–S batteries, most reported electrocatalysts are nonchemically active and do not participate in electrochemical reactions. However, the VS 2 catalyst is different from them, in that it has typical electrochemical behaviors of lithiation and delithiation, and the Li x VS 2 intermediates play an important role in regulating polysulfide conversion . According to the previous reported work, the S vacancies in VS 2 can provide an additional transfer path that is perpendicular to the VS 2 plane and improve the ion-diffusion kinetics in VS 2– x , so it is inferred that VS 2– x can likely have high catalytic activity, which is also verified by electrochemical tests.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In Li–S batteries, most reported electrocatalysts are nonchemically active and do not participate in electrochemical reactions. However, the VS 2 catalyst is different from them, in that it has typical electrochemical behaviors of lithiation and delithiation, and the Li x VS 2 intermediates play an important role in regulating polysulfide conversion . According to the previous reported work, the S vacancies in VS 2 can provide an additional transfer path that is perpendicular to the VS 2 plane and improve the ion-diffusion kinetics in VS 2– x , so it is inferred that VS 2– x can likely have high catalytic activity, which is also verified by electrochemical tests.…”
Section: Resultsmentioning
confidence: 76%
“…However, unlike other materials, layered VS 2 catalysts have typical lithiation behavior, and the relevant lithiation potentials are in the working voltage range of Li–S, which should not be ignored. Unfortunately, most papers reporting VS 2 catalysts as nonchemically active components did not consider their dynamic evolution behavior until Wang et al reported the prominent Li + intercalation process of VS 2 in Li–S batteries . According to a previous report, Li et al reported that the Li x Mo 6 S 8 intermediate shows a higher affinity to polysulfides than the original Mo 6 S 8 and thus displays strong adsorbability and good catalysis to polysulfides .…”
Section: Introductionmentioning
confidence: 99%
“…[ 56 ] Very recently, the VS 2 has also been explored to show the same mechanism when used as a polysulfide regulator. [ 57 ] In addition to metal sulfides, some pseudocapacitive metal oxides also show similar properties. For example, orthorhombic Nb 2 O 5 and birnessite MnO 2 were applied as desirable electron/ion sources during the chemical redox reactions of sulfur.…”
Section: Reaction Principles and Characterizations Of Psrcsmentioning
confidence: 99%
“…To mitigate the shuttle effect and improve the reaction kinetics, researchers investigated several metal-based (metal, metal oxides/sulfides/nitrates, etc.) and metal-free adsorbents as catalytic additives. In this regard, metal oxides with mixed oxidation states were found to be suitable cost-effective polysulfide adsorption and conversion catalysts as the metal centers and polar O 2‑ sites chemically interact with LiPS. Particularly, the metal oxides with hollow structures could efficiently trap polysulfides through strong physical and chemisorption. Further, the inner void space of the hollow sphere accommodates large volume changes during the charge–discharge process. , Gao et al reported V 2 O 5 (V-metal center) hollow microspheres with graphene carbon network heterostructures as cathode hosts for Li–S batteries.…”
Section: Introductionmentioning
confidence: 99%